Vision based obstacle avoidance for mobile robot using optical flow process - Mohd Shah, Hairol Nizam; Kamis, Zalina; Abdollah, Mohd Fairus; Khamis, Alias; Mohd Aras, Mohd Shahrieel; Baharon, Mohd Rizuan; Ifwat, Nor Azni (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
The paper is discuss on develop and implement a vision based obstacle avoidance for mobile robot using optical flow process. There are four stages in this project which are image pre-processing, optical flow process, filtering, object stance measuring and obstacle avoidance. The optical flow process are an image resizing, set parameters, convert color to grayscale, Horn-Schunk method and change grayscale image to binary number. Next process is a filtering done by smoothing filter then image center will be defined. The maximum distance object from a camera has been set as 20 cm. Therefore, the decisions of the robot to move whether left or right are based on the direction of optical flow. This avoidance algorithm allows the mobile robot to avoid the obstacles which are in different shape either square or rectangular. A friendly graphical user interface (GUI) had been used to monitor the activity of mobile robot during run the systems.